PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE JIGSAW TERHADAP HASIL BELAJAR SISWA - Felisia Reformasi Daeli (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2024)
This research is motivated by the learning results of students in class VIII of SMP Negeri 4 Lahomi for the 2023/2024 academic year, that the increase in learning outcomes of students who are less active in learning is caused by the learning model used. The aim of this research is to determine the improvement in student learning outcomes through the application of the Jigsaw Type Cooperative Learning model in social studies subjects. This type of research is classroom action research (PTK), the subjects of this research are class VIII, totaling 28 people. The instruments used were learning outcomes tests, observation sheets and photo documentation. Based on the results of observations of teacher activities and student activities, learning improvements were obtained. For observations in cycle I, student learning outcomes increased from 57.14% to 78.75% in cycle II. And observing student activities increased from 69.57% in cycle I to 92.8% in cycle II. Student learning completion in cycle I was 69.57, but still did not meet the criteria for learning completeness. In cycle II, learning through the jigsaw type cooperative learning model experienced an increase with students' learning completeness being 100%, so they had met the criteria for learning completeness. Based on the level of student learning success, this has achieved the target of success. The conclusion of this research is that by implementing the jigsaw type cooperative learning model, student learning outcomes improve very well. Suggestions from researchers are that teachers should apply the Jigsaw Type Cooperative Learning Model to implement competency standards and basic competencies in social studies subjects systematically so that students master them completely and the results of this research should be used as comparison material for other researchers.